7 Youth gambling and mental health- a population study. (18th November 2019) - Emond, A; Griffiths, M; Hollen, L
Abstract : Aims: To investigate gambling behaviour in youth aged 17-24 and explore the associations with mental health and wellbeing. Methods: A large contemporary UK cohort study, the Avon Longitudinal Study of Parents and Children (ALSPAC), was used to collect the data. Young adult participants completed computer-administered gambling surveys in research clinics, on paper and online. Depression, anxiety and wellbeing scores, and drug and alcohol usage, were collected by self-completion questionnaires. The sample sizes were 3566 at age 17 years, 3940 at 20 years, and 3841 at 24 years. Multiple imputation techniques were utilised to adjust for missing data, and multivariable models created using the imputed data set. Results: Participation in gambling in the last year was reported by 54% of 17-year-olds, rising to 68% at 20 years, and 66% at 24 years, with little overall variance. Regular (weekly) gambling showed a strong gender effect, increasing from 13% at 17 to 17% at 24 years. The commonest forms of gambling were playing scratchcards, playing the lottery, and private betting with friends. The only activity which increased markedly between 17 and 24 years was gambling on activities via the internet, especially in males. Problem gambling was measured at each age using the Problem Gambling Severity Index (PGSI), and responses categorised into 'no problem' 'low risk gambling' (16-21%) and 'moderate risk/problem gambling' (6-7%). At risk gamblers had shown higher hyperactivity scores and conduct problems on the SDQ at 16 years. Between 17 and 24 years, any at risk gambling was associated with higher depression and anxiety scores, and wellbeing scores in the lowest quartile. The adjusted odds ratios (95% CI) were highest in the moderate/problem group at 20yrs: depression 2.29 (1.28, 4.12), low wellbeing 1.61 (1.01, 2.57), involvement in crime 2.47 (1.54, 3.97), problematic use of alcohol 2.64 (1.13, 6.17), and drug use 1.79 (1.16, 2.75). Problem gamblers were more likely to have parents who gambled. Conclusion: Although many young people gamble without any harm, a significant minority (mainly males) show problem gambling behaviours which are associated with poor mental health, low wellbeing, and potentially harmful use of drugs and alcohol.